β-glucan signaling connects phagocytosis to autophagy - Ma, Jun (Oxford University Press, 2013)
A growing list of innate immune receptors is being defined that recognize polysaccharides of microbial cell walls. Fungal β-glucan recognition by the receptor Dectin-1 triggers inflammatory immune responses in macrophages and dendritic cells that are appropriate for defense against fungal pathogens. Among these responses is the specific recruitment of the autophagy-related protein light chain 3 (LC3) to phagosomes containing fungi. Studies documenting LC3's recruitment to phagosomes containing β-glucan and other nonsugar particles suggest that LC3 plays a role in regulating phagocytosis and its related immunological responses.